ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN HUTANG TERHADAP DIVIDEN TUNAI (Students' Journal of Accounting and Banking, 2013)
This study aims to empirically examine the factors that affect the cash dividend (DPR) of the company by using the analyzed variables that measure profitability (ROE), liquidity (CR), and debt (DER). The sample in this study are all listed manufacturing companies in Indonesia Stock Exchange (IDX) of the years 2009-2011 respectively.Sampling was purposive sampling method. The method of analysis used in this study is multiple regression analysis and using the SPSS program for data processing. The results of this study indicate that profitability (ROE) have positive and significant impact on cash dividends, liquidity (CR) have positive and significant impact on cash dividends, and debt (DER) and no significant negative effect on cash dividends manufacturing companies listed on the Stock Securities Indonesia in 2009-2011 respectively.Keywords: Profitability (ROE), Liquidity (CR), Debt (DER) and dividend (DPR).